Clinical and dermoscopic findings in 58 cases of nevus spilus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
Nevus spilus (NS) is a benign melanocytic proliferation, more or less extensive, clinically characterized by a higher concentration of melanocytic nevi which are distributed on a patch of hyperpigmented skin. Its time of onset is debated, probably because of its poor visibility in the early stages of life. The discussion is also open on the possible occurrence of melanoma of NS and therefore on its prognosis and treatment options. These topics are dealt with according to the literature and the review of 58 personal cases.